MOTIVASI BERJILBAB DALAM ISLAM DAN ‎BERMANTILA DALAM KATOLIK TERHADAP ‎KESADARAN BERAGAMA - Yani, Irma; Nur, Anwarsyah (Jurnal Ushuluddin, 2021)
The purpose of this research is to increase knowledge about the concept of wearing the hijab in Islam and the mantilla in Catholicism, to understand how to properly wear the hijab and mantilla according to Islamic and Catholic teachings, and to identify any similarities and differences between the hijab in Islam and the mantilla in Catholicism. This research aims to generate knowledge and understanding. The hijab is a long piece of cloth that extends from the top to the bottom, covering a woman’s body. However, in this study, the term hijab refers to the term commonly used and quite popular in Indonesia, which refers to the long headscarf worn by Muslim women. The motivation for wearing the hijab is a form of spiritual fulfillment that forms a religious awareness in oneself or as a need for the integration of beliefs and values. Wearing the mantilla is not particularly encouraged, but in the culture of that time, women were expected to wear a headscarf as a sign of obedience to Christ